2011
DOI: 10.2334/josnusd.53.225
|View full text |Cite
|
Sign up to set email alerts
|

Use of aminoguanidine, a selective inducible nitric oxide synthase inhibitor, to evaluate the role of nitric oxide in periapical inflammation

Abstract: The purpose of this study was to evaluate the effects of aminoguanidine (AG) as a selective inhibitor of inducible nitric oxide synthase (iNOS) on the degree of inflammatory response in periapical lesions in the canine teeth of cats. Root canals from 52 cat canine teeth were exposed to the oral cavity and sealed after 7 days. One day before pulp exposure, cats were administered either AG (experimental group) or normal saline (control group), which was continued on a daily basis until the day of sacrifice. Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…[28] Hama et al , explained the mechanisms regarding the role of NO in the progression of periapical inflammation. [29] Our research group, in the first of series of investigations on NO, demonstrated that AG administration significantly reduced the inflammatory intensity in periapical lesions of cats,[30] which was consistent with the findings of the present study. The results of the current investigation showed that AG as a selective inhibitor of iNOS can promote the healing of periapical region.…”
Section: Discussionsupporting
confidence: 91%
“…[28] Hama et al , explained the mechanisms regarding the role of NO in the progression of periapical inflammation. [29] Our research group, in the first of series of investigations on NO, demonstrated that AG administration significantly reduced the inflammatory intensity in periapical lesions of cats,[30] which was consistent with the findings of the present study. The results of the current investigation showed that AG as a selective inhibitor of iNOS can promote the healing of periapical region.…”
Section: Discussionsupporting
confidence: 91%
“…Histopathological changes were graded in a blinded manner as described previously (Farhad et al . ). The boundaries of the periapical lesions associated with the mesial roots were determined using the freehand drawing tool of the image analysis program, and the lesion area was calculated.…”
Section: Methodsmentioning
confidence: 97%
“…The histological parameters of the samples were examined using light microscopy (CX41; Olympus Corporation, Tokyo, Japan) and an image analysis program (Database Manual Cell Sens Life Science Imaging Software System; Olympus Corporation) by a physician specialized in Pathology. Histopathological changes were graded in a blinded manner as described previously (Farhad et al 2011). The boundaries of the periapical lesions associated with the mesial roots were determined using the freehand drawing tool of the image analysis program, and the lesion area was calculated.…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…[ 35 ] Farhad et al . [ 14 ] in their study on a cat model evaluated the effect of systemic administration of AG on the severity of inflammation and demonstrated that AG significantly decreased the severity of inflammation in periapical lesions. In another study, Farhad et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Farhad et al . [ 14 ] in their study on the role of NO in the progression of the inflammatory process in the periapical tissue in a cat model demonstrated that systemic administration of a selective iNOS inhibitor (AG) significantly decreased the severity of inflammation in the periapical lesions induced in the periapical region of canine teeth. Moreover, Farhad et al .…”
Section: Introductionmentioning
confidence: 99%